2014
DOI: 10.1371/journal.pone.0109675
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Identifies Phospholipase C zeta 1 (PLCz1) as a Stallion Fertility Locus in Hanoverian Warmblood Horses

Abstract: A consistently high level of stallion fertility plays an economically important role in modern horse breeding. We performed a genome-wide association study for estimated breeding values of the paternal component of the pregnancy rate per estrus cycle (EBV-PAT) in Hanoverian stallions. A total of 228 Hanoverian stallions were genotyped using the Equine SNP50 Beadchip. The most significant association was found on horse chromosome 6 for a single nucleotide polymorphism (SNP) within phospholipase C zeta 1 (PLCz1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 87 publications
(94 reference statements)
1
27
0
Order By: Relevance
“…In recent years, approximately 60 candidate genes with functional importance for male fertility have been reported (Roser, 2008;Giesecke et al, 2010;Sieme and Distl, 2012). Candidate genes for stallion fertility including ACE, CRISP3, FKBP6, FSHB, INHBA, PLCz1, PRLR, SPATA1 and SP17 have been screened for polymorphisms and tested for association with stallion fertility using estimated breeding values for the paternal component of the pregnancy rate per estrus cycle (EBV-PAT) as target trait (Giesecke et al, 2010;Sieme and Distl, 2012;Schrimpf et al, 2014Schrimpf et al, , 2015. However, genes affecting semen traits in stallions are poorly clarified.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, approximately 60 candidate genes with functional importance for male fertility have been reported (Roser, 2008;Giesecke et al, 2010;Sieme and Distl, 2012). Candidate genes for stallion fertility including ACE, CRISP3, FKBP6, FSHB, INHBA, PLCz1, PRLR, SPATA1 and SP17 have been screened for polymorphisms and tested for association with stallion fertility using estimated breeding values for the paternal component of the pregnancy rate per estrus cycle (EBV-PAT) as target trait (Giesecke et al, 2010;Sieme and Distl, 2012;Schrimpf et al, 2014Schrimpf et al, , 2015. However, genes affecting semen traits in stallions are poorly clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Candidate genes for stallion fertility including CRISP3 , SPATA1, INHBA, ACE , SP17, FSHB , PRLR and PLCz1 have been screened for polymorphisms and tested for association with estimated breeding values for the paternal component of the pregnancy rate per oestrus cycle (EBV‐PAT) in stallions (Sieme and Distl ; Schrimpf et al. ). In human, a large number of genes with influence on male fertility were evaluated (Kosova et al.…”
Section: Introductionmentioning
confidence: 99%
“…To date, approximately 60 candidate genes with functional importance for male fertility have been reported for horses (Roser 2008;Giesecke et al 2010;Sieme and Distl 2012). Candidate genes for stallion fertility including CRISP3, SPATA1, INHBA, ACE, SP17, FSHB, PRLR and PLCz1 have been screened for polymorphisms and tested for association with estimated breeding values for the paternal component of the pregnancy rate per oestrus cycle (EBV-PAT) in stallions (Sieme and Distl 2012;Schrimpf et al 2014). In human, a large number of genes with influence on male fertility were evaluated (Kosova et al 2012;Song et al 2012;Hotaling and Carrell 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although only preliminary findings, such numbers of RNA species are almost double those previously identified by Das et al (2013). MiRNA are short non-coding RNAs and function in the post-transcriptional regulation of mRNA by destabilising or supressing translation, thus impeding protein production (Jevsinek Skok et al 2013, Schrimpf et al 2014. Research into sperm miRNA expression in mice revealed that the miRNA cluster, MiR-880, plays a significant role in early embryonic development and gene regulation, as embryos generated using testicular and cauda sperm populations, which carry abundant MiR-880, developed normally, while embryos generated using sperm isolated from the caput epididymis, which are deficient in miR-880, failed soon after implantation (Conine et al 2018).…”
Section: Assessmentmentioning
confidence: 99%
“…Das et al (2013) previously identified three stallion sperm miRNAs (MIR34B, MIR34C and MIR449A) as being critical for gene expression and early embryonic development. MiRNAs are also potentially involved in the regulation of steroid synthesis during spermatogenesis, as these molecules have been indicated to function in the regulation of both Leydig and Sertoli cells in stallions (Schrimpf et al 2014). Recently, Tsatsanis et al (2015) identified miR-155 as marker of subfertility in men; therefore, it is conceivable that sperm miRNA expression may be developed in the future as a diagnostic tool reflective of sperm fertilisation capacity.…”
Section: Assessmentmentioning
confidence: 99%